Implications of Corporate Sustainability Reporting Directive (CSRD) to Company Network Collaboration - Jokinen, Leena; Harju, Noora; Kinnunen, Kalle; Hänninen, Saara (Hapres, 2025)
This paper examines the collaborative dynamics within a European cruise shipbuilding company network, with a particular focus on sustainable development (SD) initiatives and compliance with the Corporate Sustainability Reporting Directive (CSRD). Shipbuilding is characterized by highly complex supplier networks, posing challenges for CSRD implementation, particularly in reporting indirect (Scope 3) greenhouse gas emissions (GHG) across the value chain. The mandatory inclusion of Scope 3 emissions requires companies to account for previously overlooked activities, posing significant resource demands due to the complexity of global supply chains. The findings highlight challenges in the preparedness of case companies for CSRD-compliant Scope 3 emissions reporting, particularly regarding necessary operational and collaborative changes. Network analysis reveals that the case company network is loosely connected, with limited interorganizational SD initiatives. While the lead company occupies a central position in advancing sustainability efforts, the overall network structure exhibits weak coordination. Despite a social framework that facilitates information exchange, the network demonstrates limited capacity to leverage collective resources for integrated reporting, development, and innovation. The findings suggest that a more open and balanced network structure, coupled with coordinated collaboration, is essential for effectively addressing CSRD requirements. Strengthening transparency, fostering commitment, and enhancing joint SD initiatives may provide strategic advantages and contribute to long-term business sustainability and renewal.